Influences on urban freight transport policy choice by local authorities. (March 2019) - Akgün, Emine Zehra; Monios, Jason; Rye, Tom; Fonzone, Achille
Abstract: Individual freight transport policies have been investigated in the literature extensively in the last 10–15 years, yet there has surprisingly been very little attention to the process of selecting urban freight transport (UFT) policy measures. This study focuses on UFT policy choice by local authorities, investigating how policy context, resource availability and the need for legitimacy influence how local authorities seek and select UFT specific policies. The methodology is a cross-case analysis of eleven cities across three countries (Sweden, England and Scotland), based on interview and documentary data. Findings reveal that all cities have the same high-level goals, such as reducing emissions and congestion, supporting the economy and improving quality of life. However, in most cases these rather general goals are not broken down into clear objectives with targets that can be measured. Therefore, selected UFT policy measures are chosen from a pool of common measures (primarily access restrictions such as time windows and weight restrictions), but without monitored targets that determine whether or not they are achieving objectives. This does not necessarily mean that the measures chosen are inappropriate, but that there is a lack of a strategic approach to setting and reviewing measures according to achieving specific policy goals. This is primarily a result of a lack of resources and dedicated UFT personnel, as well as challenges related to public acceptability of restrictive policies. Highlights: All cities have the same high-level goals, such as reducing emissions and congestion. Goals are not broken down into clear objectives with targets that can be measured. UFT measures chosen from a pool of commonly accepted measures. Main challenges were a lack of dedicated UFT personnel and public acceptability. Need for increased learning from and collaboration with private sector operators.